Mathematics Proficiency -- A Systematic Literature Review - Helsa, Yully; Juandi, Dadang; ., Turmudi (KnE Social Sciences, 2024)
There have been a significant number of studies on mathematical proficiency; however, there are no classifications on research related to it. This study aims to gather and analyze previous studies on mathematical proficiency based on its publication year, research subject, methods, and results. This research is a survey-based descriptive study using the SLR method. The survey was conducted with secondary data in the form of research articles on mathematical proficiency at all educational levels, teachers and students were also included from 2010 to 2020. The steps included in this research were data collection, data analysis, and conclusion. Collected data were in the form of research articles published in international journals and proceedings indexed in Scopus and other trusted databases, such as Thomson, Google Scholar, Science Direct, and Eric databases. The results show that the majority of research on mathematical proficiency was the ones performed in the year 2019 with percentages of 20% and 16%, and the most significant subject were junior high school students with 21%. Results on mathematical proficiency were based on the level of proficiency, positive and negative correlations between mathematical proficiency and other variables, efforts in improving mathematical proficiency, and the assessment of mathematical proficiency. The results suggest that this research could support further studies on mathematical proficiency. Keywords: mathematics proficiency, systematic literature review